Tendentious Actions, Racism, or Bad Prejudice?: Examining the Relations of Ethnocentrism and Xenophobia in the Contemporary South Korea - Darynaufal Mulyaman; Achmad Ismail (Andalas Journal of International Studies (AJIS), 2021)
When the phenomenon of contemporary South Korean culture in the world goes viral, some content can be regarded as tendentious content in the receiving countries. While some of these countries have large potential markets for South Korean commodities, including contemporary culture, these seem untouched by some of the tendentious prejudices exercised by South Korean. This research will emphasize the answer to the question of South Koreans who often take tendentious actions towards other countries/cultures? This article argues that the acts of prejudice committed by South Koreans are due to the high ethnocentric attitudes of South Korean society. Even when it became controversial, in the end, South Korea did not care much about cultural sensitivity to the culture of other countries. This article uses the concept of ethnocentrism as an answer to the frequent actions of either racism or things that tend to be in South Korean society. The findings confirm that the tendentious act of South Korean society stems from their feelings of cultural superiority by looking down on other cultures since Korea was colonized and is now a country with a more developed economy.